Implementasi Congestion Avoidance pada HWMP dengan menggunakan CCNF dan Queue Threshold pada Jaringan VANET - Audi Azzura Falaq; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Vehicular Ad hoc Network (VANET) is prone to experience congestion problems. The congestion may cause the packet to be stuck, and fails to arrive at its destination. In this study, modifications to the HWMP protocol will be carried out to overcome the congestion problem. The modification made is to apply a threshold to monitor the queue at the node. If a node is starting to get congested, the node will send a Congestion Control Notification Frame (CCNF) to other nodes. The CCNF function is to notify other nodes that the node cannot receive packets for a while. So that an alternative route that excludes the congested node will be formed. Tests will be carried out on 3 different mobility models, namely, the Manhattan model, the Freeway model, and the real map. From those test, 4 parameters such as average end-to-end delay, packet delivery ratio (PDR), throughput, and normalized routing load will be measured. Based on the results of the tests, it is known that the modified protocol is superior in PDR and throughput, but there is a decrease in performance in average end-to-end delay and normalized routing load.